Increasing the Efficiency of High-tech Companies Based on Interactions with the Entities of the Innovative Environment - Doroshenko, Yury Anatolievich; Starikova, Maria Sergeevna; Somina, Irina Vladimirovna; Malykhina, Irina Olegovna (Economy of Regions, 2019)
Competitive relations’ modification, digital space’s development, markets’ over-fragmentation, technological and economic convergences, complexity of search for market niches cause an increase in the volume and depth of interactions with representatives of the innovative environment for maintaining and strengthening the positions of market leaders. Primarily, this problem concerns high-tech companies, because they shape new markets and create products, satisfying latent needs. Increase in the volume of contacts arising from the establishment of the innovative production creates a problem of optimising business interactions as a condition for increasing the business’ efficiency. For solving this problem, the article summarises the theoretical and methodological aspects of shaping the effective portfolio of interactions between high-tech sector and entities of the innovative environment. Based on the regression analysis, we proved the low efficiency of Russian innovations in forming the opportunities for conquering world markets. We analysed the performance indicators of state programs and strategies. The analysis demonstrated a low level of the innovation leadership of Russian high-tech sector. Thus, it confirmed the hypothesis about the necessity of rationalising relationships and using substantiating models of cooperation between high-tech sector and entities of the innovative environment. We suggested a toolkit for assessing the enterprises’ efficiency and their dependence on the entities of the innovative environment. The toolkit is based on expert measurements using quantitative linguistic scales. We developed these scales as they simplify the procedure of identifying the mutual compliance, interest, satisfaction with the cooperation between high-tech companies and representatives of the innovative environment. Using the obtained methodology, we proposed the optimal structure of the four identified models of interaction between high-tech companies and the innovative environment. The models were named by analogy with the styles of modern dance (hustle, contemporary, lindy hop, zouk). The further research can focus on assessing sustainability and determining the life cycle of cooperation with entities ofthe innovative environment.